2019
DOI: 10.29252/beat-070102
|View full text |Cite
|
Sign up to set email alerts
|

Features and Results of Conducted Studies Using a Lean Management Approach in Emergency Department in Hospital: A Systematic Review

Abstract: Objective:To perform a systematic review of the properties and results of the studies that their approaches are lean management in emergency departments and the factors which influence on their performance. Method:The necessary information in the first stage was collected by searching these keywords: "Lean principles" “Lean Six Sigma", "Lean Process", “Lean thinking”, “Lean Methodology”, “Toyota Production System lean processing”, "lean techniques", "emergency department”, “emergency medicine”, “emergency roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 60 publications
0
17
0
2
Order By: Relevance
“…Reduction in assistance time is crucial and directly impacts patient satisfaction, especially in emergency services. A review study that highlighted a greater number of improvements related to reduction in length of hospital stay, waiting time, volume of care and increased satisfaction, corroborates the statement (42) .…”
Section: Discussionmentioning
confidence: 56%
“…Reduction in assistance time is crucial and directly impacts patient satisfaction, especially in emergency services. A review study that highlighted a greater number of improvements related to reduction in length of hospital stay, waiting time, volume of care and increased satisfaction, corroborates the statement (42) .…”
Section: Discussionmentioning
confidence: 56%
“…These principles and waste are the theoretical foundations that constitute lean manufacturing philosophy [28]. With this, it is already known that lean is a philosophy that has been increasingly implemented in the health area over the past years [9]. With the results obtained through this review, it was possible to verify which tools are being used more in this area and which are the main results achieved.…”
Section: Discussionmentioning
confidence: 85%
“…The studies found were published, predominantly, in the English language, probably due to the fact that the majority were carried out in the United States, one of the pioneers in the application of lean healthcare [9]. The second country that published the most research on the subject was Brazil, demonstrating that lean has been the target of growing interest in the country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( Arkader and Janeiro, 2001;Deloitte and Touche, 2002;Hacker and Doolen, 2005;Radnor and Walley, 2008;Radnor and Boaden, 2008;Scorsone, 2008;Young and McClean, 2009;Suárez-Barraza and Ramis-Pujol, 2010;Poksinska, 2010;Grove et al, 2010;Wong and Wong, 2011;Eswaramoorthi et al, 2011;Scherrer-Rathje, 2012a, 2012b;Machado Guimarães et al, 2013;Rymaszewska, 2014;Dora et al, 2014;Sisson and Elshennawy, 2015;Zimmermann and Bollbach, 2015;Matthias and Brown, 2016;Cherrafi et al, 2016;Sahai, Virmani and Saha, 2017;Pearce et al, 2018;Rexeisen et al, 2018;Tezel et al, 2018;Thanki and Thakkar, 2018;De Oliveira et al, 2018;Caldera et al, 2019;Isfahani et al, 2019;Sindhwani et al, 2019;Gao and Gurd, 2019) Resources constraints  Budget constraints;  Financial (Er et al, 2000;Bateman and Rich, 2003;Canadian…”
mentioning
confidence: 99%